On Starting Control of Vibrations of a String - Tukhtasinov, M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Within the framework of the theory of games, we consider the problem of starting control of oscillations of points of a string according to a given law. As control parameters for players, the initial position and the starting velocity of the string are taken. We determine the optimal control for players in both discrete case and continuous case.